Pengembangan E-Lkpd Discovery Learning Berbasis Etnosains Lampung Traditional Food Untuk Meningkatkan Keterampilan Proses Sains Peserta Didik Pada Materi Sistem Pencernaan Di SMP - Zelviana, Eva; Sunyono; Lengkana, Dewi (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the perception of science teachers towards e-LKPD discovery learning based on ethnoscience Lampung Traditional Food to improve students' science process skills on the Digestive System material in junior high school. The study was conducted in Tanggamus district, involving ten respondents of science teachers and 50 students. The method study is a mixed method with Sequential Explanatory Design which combines data collection and data analysis qualitatively and quantitatively. Data was taken using questionnaires. The survey results that 0% of science teachers did not know ethnoscience-based e-LKPD, 80% of science teachers stated that the LKPDÂ  that had been used had not trained students' science process skills, and 100% of science teachers stated that it was necessary to develop ethnoscience-based e-LKPD teaching materials. Based on student response questionnaires, 0% stated the LKPD used had not grown science process skills, and 100% of students needed other learning resources, namely ethnoscience-based e-LKPD. Teachers and students in Tanggamus Regency have never used ethnoscience-based e-LKPD, especially regarding the traditions of the Lampung people. Based on these results, concluded that e-LKPD discovery learning based on ethnoscience Lampung Traditional Food is needed to improve the science process skills of students in junior high school.